The Role of Cangkruk Culture in Developing Skills and Creativity of Junior Graphic Designers in Surakarta - Kusuma, Rizqi Fajar; Martadi, Martadi; Sabri, Indar; Suryandoko, Welly; Agista, Yogha Adhi (Graduate School of Institut Seni Indonesia Yogyakarta, 2025)
The Javanese culture of Cangkruk, a tradition of casual social interaction, has a positive chain effect for aspiring graphic designer students. This research aims to analyze the role of Cangkruk in developing creativity in junior graphic designers in Surakarta. The method used is a case study on students majoring in fine arts education at Sebelas Maret University, with a Peer Teaching approach and analysis of the creativity process according to Wallas, which includes four stages, which are preparation, incubation, illumination, and verification. This research found that Cangkruk culture functions as a space that supports peer learning and collaboration, a medium for reflection and design criticism, a source of inspiration and creative exploration, as well as emotional support and motivation. The creative process that occurs in Cangkruk allows designers to learn through real practice based on social interaction. By creating an open space that encourages dialog of ideas, collaboration, and reflection of design work, it can enrich the creative process to produce creative products that are compatible with the design industry. In conclusion, cangkruk can be positioned as an alternative pedagogical tool or informal learning space in developing the skills and creativity of junior graphic designers. This research recommends further exploration of the potential of Cangkruk culture in other disciplines and diverse cultural backgrounds and institutions. Peran Budaya Cangkruk dalam Mengembangkan Keterampilan dan Kreativitas pada Desainer Grafis Junior di Surakarta Abstrak Budaya Cangkruk merupakan tradisi masyarakat Jawa berupa interaksi sosial santai, memiliki efek berantai positif bagi mahasiswa calon desainer grafis. Penelitian ini bertujuan untuk menganalisis peran Cangkruk dalam mengembangkan kreativitas pada desainer grafis junior di Surakarta. Metode yang digunakan adalah studi kasus pada mahasiswa jurusan pendidikan seni rupa di Universitas Sebelas Maret, dengan pendekatan Peer Teaching dan analisis proses kreativitas menurut Wallas, yang meliputi empat tahap, yaitu persiapan, inkubasi, iluminasi, dan verifikasi. Penelitian ini menemukan bahwa budaya Cangkruk berfungsi sebagai ruang yang mendukung peer learning dan kolaborasi, media refleksi dan kritik desain, sumber inspirasi dan eksplorasi kreatif, serta dukungan emosional dan motivasi. Proses kreatif yang terjadi dalam Cangkruk memungkinkan desainer untuk belajar melalui praktek nyata berbasis interaksi sosial. Dengan menciptakan ruang terbuka yang mendorong dialog ide, kolaborasi, dan refleksi karya desain dapat memperkaya proses kreatif untuk menghasilkan produk kreatif yang seusai dengan industri desain. Kesimpulannya, cangkruk dapat diposisikan sebagai alat pedagogis alternatif atau ruang pembelajaran informal dalam pengembangan keterampilan dan kreatifitas desainer grafis junior. Penelitian ini merekomendasikan eksplorasi lebih lanjut terhadap potensi budaya Cangkruk dalam disiplin ilmu lain dan latar belakang budaya serta institusi yang beragam.